Infrastructures de transport hybrides : quelques enseignements pour la planification. Le cas de la ligne de métro automatique Météor à Paris - Geneviève Zembri (Belgeo)
A complex decision-making process and uncertain results characterize hybrid transport infrastructures. The article analyses the decision-making process of a case study (Météor, automatic metro line, Paris) and shows how a transport project can become hybrid (technically, spatially, etc). The main results show that hybridity depends more on the conditions of the decision-making process than on the nature of the risks of the project. Hybridity can generate opportunities and risks as lack of connectivity, problems of decision scale in the case of a multiscalar project (as Météor, etc). These risks can be decreased by the choice of one decision level. But this should be compatible with different levels of financing. Hybridity can generate risks which depend on the lack of a global transport and land planning policy.